ANALISIS PSBB (PESTA HASANAH BERBAGI BAHAGIA) BNI SYARIAH SOLUSI DIMASA PANDEMI COVID 19 - Itsnaini Chusnul Khotimah (LA RIBA: Jurnal Perbankan Syariah, 2020)
This research aims to describe the BNI Syariah PSBB (Party of Hasanah Sharing) program during the COVID-19 Pandemic. Covid 19 has affected various aspects of people's lives in Indonesia. One of them is the weakening economic aspect. The Central Statistics Agency (BPS) for the August period stated that economic growth in Indonesia in the second quarter of 2020 was minus 5.32%. However, for the banking aspect, the capital of the banking industry increased 23.2% from July 22.96%. And Islamic banking itself has experienced a growth of 9.22% from 2019. PSBB is one of the BNI Syariah programs to increase DPK. What is known that BNI Syariah during the COVID 19 pandemic experienced an increase in TPF by 21.76% year on year (YOY) in the third quarter of 2020. The author uses descriptive qualitative research methods based on the theory obtained through study literature. The results of this study indicate that the PSBB (Pesta Hasanah Berbagi Bahagia) program as a program to increase TPF at BNI Syariah has been said to be successful. Where many customers deposit their funds in BNI Syariah through the PSBB (Pesta Hasanah Berbagi Bahagia) program. Because the PSBB (Pesta Hasanah Berbagi Bahagia) program uses a type of Mudharabah and Wadiah contract with three products, namely BNI Prima iB Hasanah, BNI Bisnis iB Hasanah and BNI iB Hasanah. Another reason customers choose PSBB (Pesta Hasanah Berbagi Bahagia) is that at the beginning of the Top Up, the customer has immediately received a gift in the form of goods, received his loyal monthly profit sharing and locked deposits for only 3 months.